Betaine Supplementation and Milk Production during Heat Stress in Crossbred Cows - Shankhpal, Sachin S; Waghela, Chanchal R; Sherasia, Pankaj L; Srivastava, Ajay K; Sridhar, V (Indian Journal of Animal Nutrition, 2018)
Present study was conducted to evaluate the effect of supplementing betaine on milk production in 20 early lactating (30-35 days in milk) crossbred cows (HF X Jersey) during hot summer months (April to July, 2018) in Anand district of Gujarat state. Cows yielding 18-20 kg milk per animal per day were divided into two groups of ten each, based on milk yield, fat% and stage of lactation. The animals in both the groups were fed basal diet, comprising of 9.0 kg concentrates, 25.0 kg green fodder and 3.5 kg dry fodder. In addition to basal diet, animals in experimental group were supplemented betaine hydrochloride @ 30 g/day and buffer @ 100 g per day for 90 days. The average temperature-humidity index was 71.78 and 78.12 at 09:00 and 14:00 hrs, respectively. Study revealed that betaine supplementation improved DMI and milk yield significantly (P<0.01) by 8.79 and 10.55% in cows as compared to control group. Average fat (3.70% vs 3.96%; P<0.01) and SNF (8.54% vs 8.63%; P<0.01) were also higher in experimental group. Lower DMI (14.2 and 15.7 kg/day) and milk yield (15.4 and 17.4 kg/day) were observed in both the groups when there was higher THI (83.3) during the study. Rectal temperature (103.4 vs 102.6 ÂºF), respiration rate (63.5 vs 45.5 per min) and pulse rate (76.8 vs 60.8 per min) at 14:00 hr were significantly (P<0.05) lower in cows supplemented with betaine, as compared to control group. The net daily income was higher by Rs. 20.05 (P<0.05) in experimental group, as compared to control. Present study indicates that the supplementation of betaine hydrochloride and buffer in the ration of dairy cows during heat stress period not only helps maintaining daily DMI and milk yield, but also helps improving net daily income of dairy farmers in tropical conditions of India.